2020
DOI: 10.1002/ajb2.1463
|View full text |Cite
|
Sign up to set email alerts
|

The role of auxin in developmentally regulated programmed cell death in lace plant

Abstract: PREMISE:Lace plant (Aponogeton madagascariensis) leaves are remodeled via developmental programmed cell death (PCD) to produce perforations located equidistantly between longitudinal and transverse veins. Auxin has been implicated in other developmental PCD processes in plants; however, the role of auxin in perforation formation in lace plant is unknown. Here the role of auxin in developmental PCD in lace plant was studied using two auxin inhibitors N-1-naphthylphthalamic acid (NPA), an auxin transport inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Phytohormone signal transduction is likely the prevailing mechanism responsible for upstream regulation of PCD processes [7]. For example, ethylene is responsible for leaf senescence and root deterioration in maize [11,12]; auxin is responsible for developmentally-regulated PCD in lace plant [32]; GA is related to both aleuronal and tapetal PCD [14,15]; the combination of auxin, cytokinin, and BR are related to PCD of TEs [33]; and JA and SA are related to both aerenchyma formation and leaf senescence [18,19].…”
Section: The Role Of the Ethylene Signaling In Replaceable Bud Pcd Of...mentioning
confidence: 99%
“…Phytohormone signal transduction is likely the prevailing mechanism responsible for upstream regulation of PCD processes [7]. For example, ethylene is responsible for leaf senescence and root deterioration in maize [11,12]; auxin is responsible for developmentally-regulated PCD in lace plant [32]; GA is related to both aleuronal and tapetal PCD [14,15]; the combination of auxin, cytokinin, and BR are related to PCD of TEs [33]; and JA and SA are related to both aerenchyma formation and leaf senescence [18,19].…”
Section: The Role Of the Ethylene Signaling In Replaceable Bud Pcd Of...mentioning
confidence: 99%
“…A recent study provided evidence for the involvement of auxin signalling in another type of developmental plant PCD programme. Denbigh et al [31] convincingly showed the role of auxin in the induction and/or execution of developmental PCD during leaf morphogenesis in lace plant [31]. PCD modulates lace plant leaf development by producing distinct perforations between longitudinal and transverse veins, offering an unique and elegant model system for studying the timing and regulation of the cell death process [96].…”
Section: To Die or Not To Die? Auxin-mediated Modulation Of Plant Pcd...mentioning
confidence: 99%
“…PCD modulates lace plant leaf development by producing distinct perforations between longitudinal and transverse veins, offering an unique and elegant model system for studying the timing and regulation of the cell death process [96]. Chemical inhibition of auxin transport and signalling, at levels not affecting the plant growth itself, prevented the hallmark PCD features, such as release of mitochondrial cytochrome c and ROS accumulation, and resulted in fewer, to no, perforations [31]. The spatio‐temporal tracking of auxin gradients during lace plant leaf perforation formation, for example, by using immunolocalization, would provide further insights into how auxin regulates this type of developmental PCD.…”
Section: To Die or Not To Die? Auxin‐mediated Modulation Of Plant Pcd...mentioning
confidence: 99%
See 1 more Smart Citation
“…This pigmentation disappears as leaves mature and chlorophyll pigmentation becomes more prominent (Figure 1C). The lace plant is an excellent model system for studying developmentally regulated PCD in planta due to the accessibility and predictability of perforation formation, the suitability of its thin and semi-transparent leaves for live cell imaging, and the established sterile culture system for propagation [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%